2013
DOI: 10.1111/2049-632x.12115
|View full text |Cite
|
Sign up to set email alerts
|

Rothia dentocariosainduces TNF-alpha production in a TLR2-dependent manner

Abstract: Previous work suggested that Rothia dentocariosa is associated with periodontal inflammatory disease. However, little is known about the pathogenicity of this bacterium. To characterize host response to this bacterium, we measured (via ELISA) the amount of TNF-α in the culture supernatant following the stimulation of THP-1 cells (a human acute monocytic leukemia cell line) with R. dentocariosa cells (ATCC14189 and ATCC14190). Exposure to bacterial cells induced the production of TNF-α in a dose-dependent manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 30 publications
2
23
1
1
Order By: Relevance
“…In addition, our findings demonstrate for the first time the inhibitory effect of hydroalcoholic pomegranate extracts on R. dentocariosa , isolated from dental plaque, a bacterium considered as one of the main etiological agents of several oral diseases, including tooth decay [ 5 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 96%
“…In addition, our findings demonstrate for the first time the inhibitory effect of hydroalcoholic pomegranate extracts on R. dentocariosa , isolated from dental plaque, a bacterium considered as one of the main etiological agents of several oral diseases, including tooth decay [ 5 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 96%
“…Earlier studies showed that inflammation, insulin resistance, and impaired glucose tolerance are positively associated with Blautia (14,25), Rothia (26), and Bilophila (27) and negatively associated with Bacteroides, Parabacteroides (28), and Acinetobacter (29). In our study, we found that Blautia, Rothia, and Bilophila were less abundant whereas Bacteroides, Parabacteroides (28), and Acinetobacter were more abundant in T1 than in T2 in normoglycemic women, which is consistent with the increase in insulin resistance seen as pregnancy progressed.…”
Section: Discussionmentioning
confidence: 99%
“…dentocariosa [ 63 ], and was first isolated from carious dentin in humans. It is mostly found in the flora of the oral cavity, dental caries, and dental plaque from periodontal patients, but also in blood, respiratory secretions, abscesses, and wounds [ 53 , 62 , 64 ]. R .…”
Section: Discussionmentioning
confidence: 99%